Knowledge, attitudes and acceptability to provider-initiated HIV testing and counseling: patients’ perspectives in Moshi and Rombo Districts, Tanzania - Manongi, Rachel; Mahande, Michael; Njau, Bernard (Tanzania Journal of Health Research, 2014)
Provider-initiated HIV testing and counseling (PITC) is referred to as routine testing in a clinical setting as part of a standard programme of medical services. PITC is initiated in order to avoid missed opportunities for people to get tested for HIV. While advocated as a strategy, there is dearth of information on patients’ views on PITC in a number of districts in Tanzania. The objective of this study was to assess the knowledge, attitude and acceptability to PITC services among patients attending health care facilities in rural and urban settings in Kilimanjaro region A total of 12 focus group discussions (FGDs) were conducted with 99 (73 female and 26 male) patients enrolled into out-patient clinics in 8 (2 hospitals and 6 primary care centers) health facilities in Moshi Urban and Rombo districts in northern Tanzania. The study explored on knowledge, attitudes and acceptability of PITC, perceived benefits and barriers of PITC, and ethical issues related to PITC. Interviews were audio taped, transcribed, translated, and analyzed using Non-numerical Unstructured Data Indexing and Theorizing (NUDIST) software. Knowledge about PITC services was generally low. Compared to men, women had a more positive attitude towards PITC services, because of its ability to identify and treat undiagnosed HIV cases. HIV stigma was regarded as a major barrier to patients’ uptake of PITC. Institutional factors such as lack of supplies and human resources were identified as barriers to successful provision of PITC. In conclusion, the findings highlight both opportunities and potential barriers in the successful uptake of PITC, and underscore the importance of informed consent, counseling and confidentiality and the need for specific strategies on advocacy for the service.